Gerakan Literasi Sekolah (GLS) Melalui Program Kampus Mengajar di SD Negeri Jojogan Kabupaten Wonosobo - Luluk Silfia Elmahuna; H. Ahmad Zuhdi; Hidayatu Munawaroh (STIKes Ibnu Sina Ajibarang, 2024)
The Teaching Campus Program is a Ministry of Education and Culture program that offers Indonesian students to hone their skills according to their talents and interests. The Teaching Campus Program is to introduce students as part of improving reading learning, especially in implementing the School Literacy Movement (GLS). The School Literacy Movement (GLS) is an activity that must be carried out to support the realization of effective learning and aims to understand one's abilities through reading, listening, speaking, and writing. This study aims to determine the implementation of the School Literacy Movement (GLS) through the Teaching Campus program at Jojogan State Elementary School and to find out the supporting and inhibiting factors for Teaching Campus students in implementing the School Literacy Movement (GLS) at Jojogan State Elementary School. Using a qualitative research approach where the type of research is descriptive. Data collection techniques use observation, interviews, and documentation. In collecting field data, researchers used participant observation and interviews, followed by data analysis. The data analysis technique uses data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the School Literacy Movement through the Teaching Campus Program succeeded in running the literacy program in the school with various literacy programs. By using several stages, namely the planning stage, the implementation stage, and the evaluation stage. The supporting and inhibiting factors of this program include the existence of a teaching campus program, facilities and infrastructure, and collaboration between teachers and students. Meanwhile, the inhibiting factors of this program include the learning culture of students who are not conducive, or are not accustomed to a culture of literacy, and there is no school librarian to manage the library as a means of the Literacy Movement program at school.